Answer: The answer is: 13,428,256. Hope this helps!!
Step-by-step explanation:
The correct answer is: [B]: " (2, 5) ".
__________________________________________
Given:
__________________________________________
-5x + y = -5 ;
-4x + 2y = 2 .
___________________________________________
Consider the first equation:
___________________________
-5x + y = -5 ; ↔ y + (-5x) = -5 ;
↔ y - 5x = -5 ; Add "5x" to each side of the equation; to isolate "y" on one side of the equation; and to solve in terms of "y".
_____________________________________________
y - 5x + 5x = -5 + 5x
y = -5 + 5x ; ↔ y = 5x - 5 ;
____________________________________________
Now, take our second equation:
______________________________
-4x + 2y = 2 ; and plug in "(5x - 5)" for "y" ; and solve for "x" :
_____________________________________________________
-4x + 2(5x - 5) = 2 ;
______________________________________________________
Note, 2(5x - 5) = 2(5x) - 2(5) = 10x - 10 ;
__________________________________________
So: -4x + 10x - 10 = 2 ;
On the left-hand side of the equation, combine the "like terms" ;
-4x +10x = 6x ; and rewrite:
6x - 10 = 2 ;
Now, add "10" to each side of the equation:
6x - 10 + 10 = 2 + 10 ;
to get:
6x = 12 ; Now, divide EACH side of the equation by "6" ; to isolate "x" on one side of the equation; and to solve for "x" ;
6x/6 = 12 / 6 ;
x = 2 ;
_________________________________
Now, take our first given equation; and plug our solved value for "x" ; which is "2" ; and solve for "y" ;
_____________________________________
-5x + y = -5 ;
-5(2) + y = -5 ;
-10 + y = -5 ; ↔
y - 10 = -5 ;
Add "10" to each side of the equation; to isolate "y" on one side of the equation; and to solve for "y" ;
y - 10 + 10 = -5 + 10 ;
y = 5 .
_____________________________
So, we have, x = 2 ; and y = 5 .
____________________________
Now, let us check our work by plugging in "2" for "x" and "5" for "y" in BOTH the original first and second equations:
______________________________
first equation:
-5x + y = -5 ;
-5(2) + 5 =? -5?
-10 + 5 =? -5 ? YES!
______________________
second equation:
-4x + 2y = 2 ;
-4(2) + 2(5) =? 2 ?
-8 + 10 =? 2 ? Yes!
_______________________________________________________
So, the answer is:
___________________________________________________________
x = 2 , y = 5 ; or, "(2, 5)" ; which is: "Answer choice: [B] " .
___________________________________________________________
The value of y in the triangle is 6°.
<h3>How to calculate the value of y in the triangle?</h3>
Firstly, it's important to note that a triangle has the total angles of 180°.
Based on the information, the triangle has interior angle measures of 11y, 10y + 10°, and 10y - 16º.
The value of y in the triangle will be illustrated thus:
11y + 10y + 10 + 10y - 16 = 180
31y - 6 = 180
31y = 180 + 6.
31y = 186
Divide.
y = 186 / 31
y = 6
The value of y is 6.
Learn more about triangles on:
brainly.com/question/17335144
#SPJ1
Answer:
no
Step-by-step explanation:
The prices are inconsistent, so there is no unique price that can be set for either an apple or an orange that will give the total prices indicated.
__
The first relation can be written as ...
$10 = 4A +4O
$10 = 4(A +O) . . . . factor out 4
$2.50 = A +O . . . . divide by 4
The second relation can be written as ...
$12 = 6A +6O
$12 = 6(A +O) . . . . factor out 6
$2 = A +O . . . . . . . divide by 6
These two relations give different prices for 1 apple and 1 orange. There is no price that can be set for either fruit that will give this result.
No unique prices can be assigned.
Answer:
y = 40 / x^1/3
Step-by-step explanation:
Given that :
y α x^1/3
y = k * 1 / x^1/3
y = k / x^1/3
When x = 125 ; y = 8
8 = k / 125^1/3
Cube root of 125 = 5
8 = k / 5
8 * 5 = k ; k = 40
Hence, expression becomes :
y = 40 / x^1/3